Experimental study and numerical analysis on mechanical behavior of GFRP-concrete composite beam - Yonghui Huang; Chenxi Shao; Shaofeng Huang; Airong Liu (Case Studies in Construction Materials)
In order to study the mechanical properties of GFRP (glass fiber-reinforced polymers)-concrete composite beam which is a new structure with potential use in coastal areas, four pure GFRP beams and seven composite beams are designed and produced in this study. Each specimen has different design parameters and their mechanical properties are investigated through experimental, numerical, and theoretical methods. Firstly, experimental results show that the ductility of the specimens will be improved by arranging the CFRP sheets on GFRP web, and the mechanical characteristics of GFRP-concrete composite beams are greatly affected by the thickness of the concrete plate. The bolt spacing not only affects the connection between concrete and GFRP but also affects the flexural performance of the composite beams. Secondly, a numerical simulation method for the composite beam using Hashin failure criteria is proposed and validated by the experiment. Comparative results demonstrate that the finite element model can precisely simulate the damage modes and load-deflection responses of composite beams. Finally, formulas for predicting the flexural and shear loading-capacity of composite beams are presented, and it exhibits an excellent agreement to the experimental results.